Arabicized Words I Surah Makkiyah - Dameg, Ausma (2009)

(untitled)
The purpose of the research about the foreign languages that pronounce Arabically in the Makiyyah surah are to know how the process happened and also to know the importance in the Arabic language. This process enlighten several important aspects such as words repetition, pronunciation, evidence and the origin of the words. To fulfill the research, I have made the reference in a lot of dependable resources. The research is definitely revealing the new word in that process. Like the al-Mu'arrab, al-Dakhil and many other words that derived from the process, for example standard can be concluded on behalf of time and language. Hence, to clarify and searching every foreign word, we must depend on the guidelines stated by the language experts. Each word that turn into Arabic must possessed certain criteria. In this research I discover about 64 more foreign words that turn into Arabic word from 17 different languages